The Role of the Directorate General of Sea Transportation in Supervision and Law Enforcement of Narcotics Trafficking in the Kuala Tanjung Port Area - Fajriansyah Marpaung; Fitri Rafianti; Mhd Azhali Siregar (Judge : Jurnal Hukum, 2026)
The increasing use of maritime transportation as a route for transnational narcotics trafficking has created significant challenges for Indonesia's maritime security and law enforcement system, particularly in strategic port areas such as Kuala Tanjung. While previous studies have primarily focused on the roles of criminal law enforcement agencies, limited attention has been given to the preventive function of the Directorate General of Sea Transportation as the authority responsible for shipping supervision. This study aims to analyze the legal authority of the Directorate General of Sea Transportation in supervising small vessels within the Kuala Tanjung Port area, examine the implementation of its supervisory function in supporting narcotics law enforcement, and identify the obstacles to optimizing its preventive role. This research employs a normative juridical method using statutory and case approaches. Legal materials were obtained through the analysis of legislation, legal doctrines, scientific literature, and relevant narcotics trafficking cases. The findings reveal that the Directorate General of Sea Transportation, through the harbormaster (syahbandar), possesses comprehensive legal authority to supervise vessel operations, verify shipping documents, conduct seaworthiness inspections, and regulate vessel departures. However, these authorities have not been fully optimized as preventive instruments against illicit narcotics trafficking due to institutional fragmentation, limited maritime surveillance facilities, insufficient inter-agency coordination, and the predominance of sectoral approaches in maritime governance. The novelty of this research lies in positioning shipping administrative supervision as an integral component of narcotics prevention rather than merely a shipping safety function. The study concludes that strengthening the preventive role of the Directorate General of Sea Transportation through integrated maritime surveillance, institutional collaboration, technological enhancement, and coordinated law enforcement policies is essential for improving the effectiveness of combating transnational narcotics trafficking in Indonesian port areas.